Bad banks choking good banks: simulating balance sheet contagion - Saed Khalil (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
We investigate the propagation of contagion through banks' balance sheets in a two-country model. We simulate an increase in non-performing loans in one bank, and study the effects on other banks and the macro-economy of each country. We show that credit crunches destabilize each economy in the short run and in the long run reduce potential output. We quantify this loss.
Keywords: E32; E37; E51; G33; 330; credit crunch; contagion; stock-flow consistent models